Intangible cultural heritage of the south-eastern Moroccan desert: rituals, traditions and living legacies of an invisible treasure - Lahcen OUKHOUYA ALI (International Journal of Scientific Research and Innovative Studies, 2025)
The intangible cultural heritage of the south-eastern Moroccan Sahara encompasses a whole world of practices, rituals and knowledge that shape the identity of local communities. In practical terms, desert rituals function as a genuine language, bringing the land to life: mobility, transhumance and collective memory are constantly intertwined within them. Hospitality, for its part, is not merely a tradition or a mechanism for survival and social cohesion, based on mutual aid and sharing in an often-harsh environment. Rituals of protection and blessing, meanwhile, help to cope with uncertainty by creating a symbolic balance between humans, nature and the sacred. Seasonal festivals, oral poetry and music, such as Ahidous, convey the group’s values, strengthen the sense of belonging and keep the collective memory alive. Rituals linked to rain, for example, demonstrate a genuine connection with the cosmos and a form of resilience in the face of drought. Tiwizi and transhumance, meanwhile, reveal a robust social organisation, where solidarity, attachment to the land and intergenerational transmission are essential. In short, all these practices form a living cultural system, indispensable for preserving identity and enabling Saharan societies to adapt to today’s changes. Keywords: Heritage – Desert ritual – Sahara – identity – symbolism. Received Date: 21 August 2025 Accepted Date: 13 September 2025 Published Date: 1 October 2025 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/716